AL-SIYAQ FI TARJAMAH KITAB AL-LUGHAH AL-'ARABIYAH ILA AL-LUGHAH AL-INDUNISIYAH - Devita Zuliati (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
In linguistic studies, there was a tremendous blow, the context in which previously did not get attention in linguistic research as it is beyond language discussion, at this time became a topic of lively discussion. Especially with the presence of London School led by Firth, he stated that the environment has a significant influence on the language. The context of the language is very helpful to understand the text and decoding. Therefore, understanding the context of non-linguistic features is indispensable. The more so in translation, because the basis of a translation is the transfer of meaning from the source language to the target language, using the appropriate context will produce a good translation. The researcher analyzed the poems in the second part of the Tata Bahasa Arab book, 53 in total. The research is a descriptive analysis in which the researcher collected data on the context and its use in translation.DOI : 10.15408/a.v3i1.2143